Things that endure: Community gardens and the post-work imaginary. (May 2023) - Schoneboom, Abigail; Mallo, Daniel; Tardiveau, Armelle
Using Gorz's writing on cities and time as a starting point, this sensory ethnographic study uses pinhole photography to explore how time feels for 'unemployed' volunteers at a community garden in the north-east of England. It upholds that the garden's ability to fill time meaningfully is grounded in the food-growing and composting cycle but is also anchored to the mature trees, structures and artworks – made, grown or maintained by the volunteers themselves, that persist in the space for many years. We argue that urban community gardens offer their denizens an 'elongated present' that is fulfilling to the individual while also sustaining community and nature. Emphasising the need for enduring, rather than temporary or pop-up, growing spaces in helping us transition to a sustainable, post-work society, the study thus adds temporal insight to existing scholarship on the importance of community gardens.